Meta-analysis across Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium provides evidence for an association of serum vitamin D with pulmonary function. Issue 10 (12th September 2018) - Xu, Jiayi; Bartz, Traci M.; Chittoor, Geetha; Eiriksdottir, Gudny; Manichaikul, Ani W.; Sun, Fangui; Terzikhan, Natalie; Zhou, Xia; Booth, Sarah L.; Brusselle, Guy G.; de Boer, Ian H.; Fornage, Myriam; et al.
Abstract: The role that vitamin D plays in pulmonary function remains uncertain. Epidemiological studies reported mixed findings for serum 25-hydroxyvitamin D (25(OH)D)–pulmonary function association. We conducted the largest cross-sectional meta-analysis of the 25(OH)D–pulmonary function association to date, based on nine European ancestry (EA) cohorts ( n 22 838) and five African ancestry (AA) cohorts ( n 4290) in the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium. Data were analysed using linear models by cohort and ancestry. Effect modification by smoking status (current/former/never) was tested. Results were combined using fixed-effects meta-analysis. Mean serum 25(OH)D was 68 (sd 29) nmol/l for EA and 49 (sd 21) nmol/l for AA. For each 1 nmol/l higher 25(OH)D, forced expiratory volume in the 1st second (FEV1 ) was higher by 1·1 ml in EA (95 % CI 0·9, 1·3; P <0·0001) and 1·8 ml (95 % CI 1·1, 2·5; P <0·0001) in AA ( P race difference =0·06), and forced vital capacity (FVC) was higher by 1·3 ml in EA (95 % CI 1·0, 1·6; P <0·0001) and 1·5 ml (95 % CI 0·8, 2·3; P =0·0001) in AA ( P race difference =0·56). Among EA, the 25(OH)D–FVC association was stronger in smokers: per 1 nmol/l higher 25(OH)D, FVC was higher by 1·7 ml (95 % CI 1·1, 2·3) for current smokers and 1·7 ml (95 % CI 1·2, 2·1) for former smokers, compared with 0·8 ml (95 % CI 0·4, 1·2) for never smokers. In summary, the 25(OH)D associations with FEV1 and FVC were positive in both ancestries. In EA, a stronger association was observed for smokers compared with never smokers, which supports the importance of vitamin D in vulnerable populations.